(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The fast development of Indian Banking Sector in therecent past has made a noteworthy contribution to India’s socio economic progressand growth. The dawn of e-transaction services at the first place andcompetition fierce amongst service providers to increase market share has beena blessing in disguise for customers. All banks in the nation areinterconnected through a widespread technology network. This dissertation willexamine the corporate governance of banks. When banks effectively gather andallocate funds, this lowers the cost of capital to firms, boosts capitalformation, and motivates productivity growth. Therefore, weak governance ofbanks echoes throughout the economy with negative consequences for economicdevelopment. After reviewing the major governance principles for banks ingeneral, this dissertation discusses two special characteristics of banks thatmake them special in practice: greater opaqueness than other industries andgreater government regulation. These characteristics weaken many traditionalgovernance mechanisms. Further, the dissertation reviews increasing evidence onwhich government policies improve the governance of banks and illustratestentative policy lessons. In total, dissertation suggests that it is imperativeto strengthen the capacity and incentives of private investors to exertgovernance over banks rather than relying greatly on government regulators.